Oxygenation indices and echocardiographic markers of pulmonary hypertension and ventricular dysfunction in congenital diaphragmatic hernia - Kamal Ali; Ibrahim Ali; Naif Alotaibi; Saleh S Algarni; Mohanned Alrahili; Mohammed Almahdi; Abdulrahman Almehaid; Saif Alsaif; Talal Altamimi; Saad Alshreedah; Mohammed Sufyani (BMJ Paediatrics Open)
Objectives To evaluate the relationship between early oxygenation indices (oxygenation index (OI) and oxygen saturation index (OSI)) and echocardiographic markers of ventricular dysfunction and pulmonary hypertension in neonates with congenital diaphragmatic hernia (CDH).Design Single-centre retrospective cohort study.Setting Level III neonatal intensive care unit at King Abdulaziz Medical City, Riyadh, Saudi Arabia.Patients A total of 47 neonates with CDH admitted between 2016 and 2024 were included. Infants with major congenital heart disease or chromosomal anomalies were excluded.Main outcome measures Correlation of OI and OSI within the first 48 hours with echocardiographic markers of ventricular function, pulmonary hypertension and Vasoactive-Inotropic Score (VIS).Results Among 47 infants, survival was 70%. Survivors had higher left ventricular ejection fraction (M-mode: 61% vs 40%, p=0.010) and more preserved speckle-tracking strain (–17% vs –11%, p=0.006). Non-survivors had elevated right ventricular systolic pressure (RVSP) (68 vs 40 mm Hg, p=0.001), greater systolic eccentricity index (1.9 vs 1.4, p=0.002) and a higher percentage of right-to-left patent ductus arteriosus (PDA) shunting (50% vs 11%, p<0.001). Higher best, mean and highest OI and OSI values were significantly correlated with impaired ventricular function, elevated RVSP and greater right-to-left PDA flow. VIS was strongly correlated with all oxygenation indices, with the strongest correlations observed for mean OSI (r=0.851, p<0.001) and mean OI (r=0.812, p<0.001). Receiver operating characteristic analysis showed that RVSP had the strongest predictive accuracy for survival (area under the curve (AUC) 0.985, sensitivity 98% and specificity 97%), followed by the percentage of right-to-left PDA shunting (AUC 0.847) and left ventricular output (AUC 0.825).Conclusions Elevated oxygenation indices within the first 48 hours are associated with biventricular dysfunction, pulmonary hypertension and higher inotropic support requirements in CDH. Integration of early oxygenation measures and echocardiographic assessment may enhance risk stratification and guide therapeutic decision-making.